INDEPENDENT WORK OF STUDENTS AS A MEANS PERSONALITY FORMATION - I.M. Shymko (Academy of Cognitive and Natural Sciences, 2007)
The article is devoted to forming of student's personality by facilities of independent educational activity on the modern stage of educational development in higher educational establishments. Problems of students' independent work which appear the process of educational activity influence on forming of personality.